Risk factors for chronic rhinosinusitis. Issue 1 (February 2015) - Min, Jin-Young; Tan, Bruce K.
<x xml:space="preserve">Abstract</x> Purpose of review To review the recent literature on risk factors for chronic rhinosinusitis (CRS) with an emphasis on genetic, comorbid diseases and environmental factors associated with CRS. Through identifying potential risk factors for CRS, we aim to glean insights into the underlying pathogenic mechanisms essential for developing effective therapeutic strategies. Recent findings Recent findings demonstrate that genetics and comorbid medical conditions including airway diseases, gastroesophageal reflux disease, inflammatory and autoimmune diseases, and various demographic and environmental factors are associated with having a CRS diagnosis. Limitations of current studies include variable application of disease definitions, lack of prospective longitudinal studies and a disproportionate focus on tertiary care populations. Summary CRS has a broad spectrum of associations ranging from genetics to comorbid diseases and environmental factors. These predisposing factors may provide valuable information for possible designing of therapeutic and preventive interventions. However, to better understand whether these associations cause CRS, further studies are needed to independently replicate findings, establish temporal relationships between exposure and disease onset, evaluate the influence of exposure dose on disease severity, and to understand the biological effects of these risk factors in the context of CRS.